PENCIPTAAN BUSANA CARNIVAL CAKRAPALAH SERTA PELATIHAN KOREOGRAFI DAN MAKEUP KECAMATAN KESAMBEN BLITAR - Syarifah Nur Hajja; M. Arif Jati Purnomo; Aan Sudarwanto (LPPM Universitas Bina Bangsa, 2023)
The community service activity entitled Creation of Busana Carnival Cakrapalah Choreography and Makeup Training in Kecamatan Kesamben, Kabupaten Blitar, was completed for 2 (two) days, namely on Saturday and Sunday, 29 and 30 July 2023 at the Kantor Kecamatan Kesamben, Kabupaten Blitar, Jawa Timur. This training activity has resulted in a Busana Carnival with the theme